High-Speed Faulted-Phase Selection Algorithm for Transmission Line Protection - Pérez, Fabián; Orduña, Eduardo; Aguilar, Rommel; Jäger, Johann (2013 26th Canadian Conference on Electrical and Computer Engineering, 2013)
A new faulted-phase selection algorithm for non-unit transmission line protection scheme is presented in this paper. The proposed algorithm employs the current signal from only one phase of three-phase system. A short time window of roughly two milliseconds is used for determining the faulted phase involved in single-phase to ground faults, so the proposed methodology can be used in high-speed transient based protection (TBP) schemes. Discrete wavelet transform (DWT) and Bayesian linear discriminant analysis are the math tools required for the algorithm. The potential of the algorithm is demonstrated with successful results obtained from extensive simulation in ATP/EMT